Political connections and corporate environmental protection-related investment: Setting a benchmark or shrinking back? - Yan Lin; Yihuan Mao; Hongtao Tan (China Journal of Accounting Studies (CJAS), 2020)
Protecting environment has become a vital responsibility for corporations. Based on manually collected data of China's A-share listed companies from 2010 to 2017, this study investigates the effìct of corporate political connections (PCs) on corporate environmental protection-related investment (EPI). Our findings suggest that PCs negatively influenc firms' EPI. Specifically, the more politically connected top executives are hired or the higher the political hierarchy of such executives, the lower would be the firm's EPI. We further find that the negative influence on EPI originates from the executives-related PCs compared with directors-related PCs. Additional tests first reveal that firms' EPI fails to prompt up corporate value. Second, the establishment of committees under the board could alleviate the negative influence of PCs on EPI. Finally, government regulation mitigates the negative effects of PCs on EPI.
Keywords: 650; Political connections; environmental protectionrelated investment; government environmental regulations